2019
DOI: 10.1155/2019/2592731
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Extraction Technology for the Seed Oil of Nigella sativa L.

Abstract: Seed oil of Nigella sativa L. is a popular edible oil in Egypt. How to improve the extraction efficiency of the oil will expand the use of the resource. In this paper, the four extraction factors, particle size of the seed, liquid-seed ratio, extraction time, and temperature, were optimized by the single-factor and orthogonal experiment to increase the extraction yield and linoleic acid concentration. The results showed that the twice extraction technology could increase the oil rate of 23.55% compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Antibacterial activity against some Bacillus species can help signify the effect on normal gut flora when oral therapy is followed. Trying different extraction protocols can help increase extraction efficiency [ 21 ]. The study on presence, extraction, and purification of thymoquinone in the local produce of black seed can be fruitful for conducting the stability studies and can help to gain maximum benefits from the bioactives.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial activity against some Bacillus species can help signify the effect on normal gut flora when oral therapy is followed. Trying different extraction protocols can help increase extraction efficiency [ 21 ]. The study on presence, extraction, and purification of thymoquinone in the local produce of black seed can be fruitful for conducting the stability studies and can help to gain maximum benefits from the bioactives.…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of N. sativa have been shown to exert anticancer, immunomodulative, anti-inflammatory, anti-bacterial, antioxidant, hypoglycemic, stomach protection, liver protection, and renal protection activities (20)(21)(22). The seeds and oil of N. sativa are widely used in food preparation and medicine (23,24). In addition, literature has shown that the co-delivery of nutrient supplements and drugs could contribute to promising results.…”
Section: Introductionmentioning
confidence: 99%